Phosphorylation of the Transactivation Domain of Pax6 by Extracellular Signal-regulated Kinase and p38 Mitogen-activated Protein Kinase - Ingvild Mikkola; Jack‐Ansgar Bruun; Geir Bjørkøy; Turiđ Holm; Terje Johansen (1999)
The transcription factor Pax6 is required for normal development of the central nervous system, the eyes, nose, and pancreas. Here we show that the transactivation domain (TAD) of zebrafish Pax6 is phosphorylated in vitro by the mitogen-activated protein kinases (MAPKs) extracellular-signal regulated kinase (ERK) and p38 kinase but not by Jun N-terminal kinase (JNK). Three of four putative proline-dependent kinase phosphorylation sites are phosphorylated in vitro. Of these sites, the serine 413 (Ser413) is evolutionary conserved from sea urchin to man. Ser413 is also phosphorylatedin vivo upon activation of ERK or p38 kinase. Substitution of Ser413 with alanine strongly decreased the transactivation potential of the Pax6 TAD whereas substitution with glutamate increased the transactivation. Reporter gene assays with wild-type and mutant Pax6 revealed that transactivation by the full-length Pax6 protein from paired domain-binding sites was strongly enhanced (16-fold) following co-transfection with activated p38 kinase. This enhancement was largely dependent on the Ser413 site. ERK activation, however, produced a 3-fold increase in transactivation which was partly independent of the Ser413 site. These findings provide a starting point for further studies aimed at elucidating a post-translational regulation of Pax6 following activation of MAPK signaling pathways. The transcription factor Pax6 is required for normal development of the central nervous system, the eyes, nose, and pancreas. Here we show that the transactivation domain (TAD) of zebrafish Pax6 is phosphorylated in vitro by the mitogen-activated protein kinases (MAPKs) extracellular-signal regulated kinase (ERK) and p38 kinase but not by Jun N-terminal kinase (JNK). Three of four putative proline-dependent kinase phosphorylation sites are phosphorylated in vitro. Of these sites, the serine 413 (Ser413) is evolutionary conserved from sea urchin to man. Ser413 is also phosphorylatedin vivo upon activation of ERK or p38 kinase. Substitution of Ser413 with alanine strongly decreased the transactivation potential of the Pax6 TAD whereas substitution with glutamate increased the transactivation. Reporter gene assays with wild-type and mutant Pax6 revealed that transactivation by the full-length Pax6 protein from paired domain-binding sites was strongly enhanced (16-fold) following co-transfection with activated p38 kinase. This enhancement was largely dependent on the Ser413 site. ERK activation, however, produced a 3-fold increase in transactivation which was partly independent of the Ser413 site. These findings provide a starting point for further studies aimed at elucidating a post-translational regulation of Pax6 following activation of MAPK signaling pathways. Pax6 is a member of the paired box-containingPax 1The abbreviations used are: Pax, paired box; GST, glutathione S-transferase; MAPK, mitogen-activated protein kinase; ERK, extracellular signal-regulated kinase; MEK, MAPK/ERK kinase; JNK, c-Jun N-terminal kinase; TPA, 12-O-tetradecanoylphorbol-13-acetate; PAGE, polyacrylamide gel electrophoresis; CAT, chloramphenicol acetyltransferase; LUC, luciferase; TAD, transactivation domain; wt, wild-type; DBD, DNA-binding domain; PVDF, polyvinylidene difluoride; CMV, cytomegalovirus; PBS, phosphate-buffered saline; PST, proline, serine, and threonine residues. gene family of transcription factors containing nine human (PAX1-PAX9) and murine (Pax1-Pax9) family members (1Strachan T. Read A.P. Curr. Opin. Genet. Dev. 1994; 4: 427-438Crossref PubMed Scopus (217) Google Scholar). The paired box was first discovered in Drosophila as encoding a conserved 125–128 amino acid paired domain unique to this family of developmental control genes (2Noll M. Curr. Opin. Genet. Dev. 1993; 3: 595-605Crossref PubMed Scopus (295) Google Scholar). Pax6 was initially cloned from human (3Ton C.C. Hirvonen H. Miwa H. Weil M.M. Monaghan P. Jordan T. van Heyningen V. Hastie N.D. Meijers Heijboer H. Drechsler M. Royer-Pokora B. Collins F. Swaroop A. Strong L.C. Saunders G.F. Cell. 1991; 67: 1059-1074Abstract Full Text PDF PubMed Scopus (749) Google Scholar), mouse (4Walther C. Gruss P. Development. 1991; 113: 1435-1449Crossref PubMed Google Scholar), zebrafish (5Krauss S. Johansen T. Korzh V. Moens U. Ericson J.U. Fjose A. EMBO J. 1991; 10: 3609-3619Crossref PubMed Scopus (187) Google Scholar), and quail (6Martin P. Carriere C. Dozier C. Quatannens B. Mirabel M.A. Vandenbunder B. Stehelin D. Saule S. Oncogene. 1992; 7: 1721-1728PubMed Google Scholar). Subsequently, the Drosophila eyeless gene was shown to be aPax6 homolog and Pax6 homologs have now been described in other invertebrates such as flatworm, ribbonworm,Caenorhabditis elegans, squid, sea urchin, and ascidian (reviewed in Ref. 7Callaerts P. Halder G. Gehring W.J. Annu. Rev. Neurosci. 1997; 20: 483-532Crossref PubMed Scopus (393) Google Scholar) as well as in amphioxus (8Glardon S. Holland L.Z. Gehring W.J. Holland N.D. Development. 1998; 125: 2701-2710PubMed Google Scholar). Pax6 is expressed in the developing central nervous system, the eyes, nose, and pancreas in higher vertebrates (4Walther C. Gruss P. Development. 1991; 113: 1435-1449Crossref PubMed Google Scholar, 5Krauss S. Johansen T. Korzh V. Moens U. Ericson J.U. Fjose A. EMBO J. 1991; 10: 3609-3619Crossref PubMed Scopus (187) Google Scholar, 9Krauss S. Johansen T. Korzh V. Fjose A. Nature. 1991; 353: 267-270Crossref PubMed Scopus (219) Google Scholar, 10Turque N. Plaza S. Radvanyi F. Carriere C. Saule S. Mol. Endocrinol. 1994; 8: 929-938Crossref PubMed Scopus (113) Google Scholar) and plays a pivotal role in the development of these organs (7Callaerts P. Halder G. Gehring W.J. Annu. Rev. Neurosci. 1997; 20: 483-532Crossref PubMed Scopus (393) Google Scholar, 11Quinn J.C. West J.D. Hill R.E. Genes Dev. 1996; 10: 435-446Crossref PubMed Scopus (195) Google Scholar, 12St-Onge L. Sosa-Pineda B. Chowdhury K. Mansouri A. Gruss P. Nature. 1997; 387: 406-409Crossref PubMed Scopus (671) Google Scholar). Loss of a functionalPax6 allele results in the Mendelian syndromes aniridia, Peter's anomaly, and congenital cataracts in man (13Hanson I. Van Heyningen V. Trends Genet. 1995; 11: 268-272Abstract Full Text PDF PubMed Scopus (166) Google Scholar) and Small eye in rodents (14Hill R.E. Favor J. Hogan B.L. Ton C.C. Saunders G.F. Hanson I.M. Prosser J. Jordan T. Hastie N.D. van Heyningen V. Nature. 1991; 354: 522-525Crossref PubMed Scopus (1168) Google Scholar). Pax6 acts high up in the regulatory hierarchy controlling eye development in both vertebrates and invertebrates (reviewed in Ref. 15Halder G. Callaerts P. Gehring W.J. Curr. Opin. Genet. Dev. 1995; 5: 602-609Crossref PubMed Scopus (190) Google Scholar). Eyeless, ribbonworm-, squid-, ascidian-, zebrafish-, or mouse Pax6are all able to induce ectopic eyes in Drosophila upon targeting their expression to different imaginal discs (16Halder G. Callaerts P. Gehring W.J. Science. 1995; 267: 1788-1792Crossref PubMed Scopus (1275) Google Scholar, 17Loosli F. Kmita Cunisse M. Gehring W.J. Proc. Natl. Acad. Sci. U. S. A. 1996; 93: 2658-2663Crossref PubMed Scopus (66) Google Scholar, 18Nornes S. Clarkson M. Mikkola I. Pedersen M. Bardsley A. Martinez J.P. Krauss S. Johansen T. Mech. Dev. 1998; 77: 185-196Crossref PubMed Scopus (126) Google Scholar, 19Tomarev S.I. Callaerts P. Kos L. Zinovieva R. Halder G. Gehring W. Piatigorsky J. Proc. Natl. Acad. Sci. U. S. A. 1997; 94: 2421-2426Crossref PubMed Scopus (160) Google Scholar, 20Glardon S. Callaerts P. Halder G. Gehring W.J. Development. 1997; 124: 817-825PubMed Google Scholar). We have recently found that zebrafish contain two Pax6 genes,Pax6.1 and Pax6.2, which are expressed in both overlapping and distinct regions during development of the eyes and the central nervous system. Both these genes are able to induce ectopic eyes in Drosophila (18Nornes S. Clarkson M. Mikkola I. Pedersen M. Bardsley A. Martinez J.P. Krauss S. Johansen T. Mech. Dev. 1998; 77: 185-196Crossref PubMed Scopus (126) Google Scholar). The paired domain is a bipartite DNA-binding domain containing an N- and a C-terminal subdomain each with a helix-turn-helix motif (21Czerny T. Schaffner G. Busslinger M. Genes Dev. 1993; 7: 2048-2061Crossref PubMed Scopus (353) Google Scholar, 22Xu W. Rould M.A. Jun S. Desplan C. Pabo C.O. Cell. 1995; 80: 639-650Abstract Full Text PDF PubMed Scopus (311) Google Scholar). Pax6, like Pax3, Pax4, and Pax7, also harbors a second DNA-binding domain, the paired-type homeodomain (2Noll M. Curr. Opin. Genet. Dev. 1993; 3: 595-605Crossref PubMed Scopus (295) Google Scholar, 7Callaerts P. Halder G. Gehring W.J. Annu. Rev. Neurosci. 1997; 20: 483-532Crossref PubMed Scopus (393) Google Scholar, 23Wilson D.S. Guenther B. Desplan C. Kuriyan J. Cell. 1995; 82: 709-719Abstract Full Text PDF PubMed Scopus (305) Google Scholar). In Pax6 this domain is separated from the N-terminal located paired domain by a flexible, acidic linker region (5Krauss S. Johansen T. Korzh V. Moens U. Ericson J.U. Fjose A. EMBO J. 1991; 10: 3609-3619Crossref PubMed Scopus (187) Google Scholar, 7Callaerts P. Halder G. Gehring W.J. Annu. Rev. Neurosci. 1997; 20: 483-532Crossref PubMed Scopus (393) Google Scholar). The region C-terminal to the homeodomain is enriched in proline, serine, and threonine residues (PST-rich) and acts as a transactivation domain (TAD) (24Carriere C. Plaza S. Caboche J. Dozier C. Bailly M. Martin P. Saule S. Cell Growth & Differ. 1995; 6: 1531-1540PubMed Google Scholar, 25Czerny T. Busslinger M. Mol. Cell. Biol. 1995; 15: 2858-2871Crossref PubMed Scopus (263) Google Scholar, 26Glaser T. Jepeal L. Edwards J.G. Young S.R. Favor J. Maas R.L. Nat. Genet. 1994; 7: 463-471Crossref PubMed Scopus (602) Google Scholar, 27Tang H.K. Singh S. Saunders G.F. J. Biol. Chem. 1998; 273: 7210-7221Abstract Full Text Full Text PDF PubMed Scopus (79) Google Scholar). It has previously been shown that quail Pax6 proteins expressed in the neuroretina are phosphoproteins and phosphoamino acid analysis revealed phosphoserine and a minor proportion of phosphothreonine (28Carriere C. Plaza S. Martin P. Quatannens B. Bailly M. Stehelin D. Saule S. Mol. Cell. Biol. 1993; 13: 7257-7266Crossref PubMed Scopus (112) Google Scholar). The activity of many transcription factors is regulated in a rapid and reversible manner by specific phosphorylation events mediated by protein kinases acting in signaling cascades initiated by extracellular stimuli (reviewed in Refs. 29Karin M. Hunter T. Curr. Biol. 1995; 5: 747-757Abstract Full Text Full Text PDF PubMed Scopus (666) Google Scholar and 30Treisman R. Curr. Opin. Cell Biol. 1996; 8: 205-215Crossref PubMed Scopus (1165) Google Scholar). Mitogen-activated protein kinases (MAPKs) are proline-directed serine/threonine protein kinases activated by heterogenous extracellular stimuli, including growth factors, hormones, cytokines, antigens, and physical-chemical stimuli such as oxidative stress, heat shock, osmotic imbalance, and UV light. MAPK cascades play essential roles in regulating many critical cellular processes, including cell growth and division, differentiation, apoptosis, and stress-related responses (reviewed in Refs. 31Robinson M.J. Cobb M.H. Curr. Opin. Cell Biol. 1997; 9: 180-186Crossref PubMed Scopus (2286) Google Scholar and 32Waskiewicz A.J. Cooper J.A. Curr. Opin. Cell Biol. 1995; 7: 798-805Crossref PubMed Scopus (535) Google Scholar). These cascades are organized into modules of three protein kinases where a MAPK kinase kinase (e.g. Raf-1) activates a MAPK kinase (e.g. MEK1) which subsequently activates a MAPK (e.g. ERK1) (31Robinson M.J. Cobb M.H. Curr. Opin. Cell Biol. 1997; 9: 180-186Crossref PubMed Scopus (2286) Google Scholar, 33Marshall C.J. Curr. Opin. Genet. Dev. 1994; 4: 82-89Crossref PubMed Scopus (902) Google Scholar). Following activation the MAPKs translocate to the nucleus to phosphorylate nuclear substrates. Currently, four distinct MAPK cascades are known in vertebrates. However, more will probably be found since the budding yeast contains five such cascades that orchestrate responses to different physiological stimuli (34Sprague Jr., G.F. Genes Dev. 1998; 12: 2817-2820Crossref PubMed Scopus (37) Google Scholar). The extracellular-signal regulated kinase (ERK) pathway mainly conveys signals from mitogenic and differentiation stimuli. The same may be true for the most recently discovered ERK5/BMK1 pathway (35Kato Y. Tapping R.I. Huang S. Watson M.H. Ulevitch R.J. Lee J.D. Nature. 1998; 395: 713-716Crossref PubMed Scopus (360) Google Scholar) while the Jun N-terminal kinase (JNK) and p38 MAP kinase pathways seems mostly involved in transducing various stress- and cytokine-triggered signals to the nucleus. In each pathway several MAPK isoforms have been found with ERK1 and -2 in the ERK pathway, JNK1–3 in the JNK pathway and p38α-δ in the p38 MAPK pathway (reviewed in Ref. 31Robinson M.J. Cobb M.H. Curr. Opin. Cell Biol. 1997; 9: 180-186Crossref PubMed Scopus (2286) Google Scholar). A growing number of transcription factors have been identified as nuclear targets for MAPK pathways (reviewed in Ref. 30Treisman R. Curr. Opin. Cell Biol. 1996; 8: 205-215Crossref PubMed Scopus (1165) Google Scholar). Thus, c-Myc (36Gupta S. Davis R.J. FEBS Lett. 1994; 353: 281-285Crossref PubMed Scopus (65) Google Scholar), Spi-B (37Mao C. Ray-Gallet D. Tavitian A. Moreau-Gachelin F. Oncogene. 1996; 12: 863-873PubMed Google Scholar), BCL-6 (38Niu H. Ye B.H. Dalla-Favera R. Genes Dev. 1998; 12: 1953-1961Crossref PubMed Scopus (248) Google Scholar), Microphthalmia (39Hemesath T.J. Price E.R. Takemoto C. Badalian T. Fisher D.E. Nature. 1998; 391: 298-301Crossref PubMed Scopus (557) Google Scholar), and several ETS-domain transcription factors such as vertebrate c-Ets1 and -2 (40Yang B.S. Hauser C.A. Henkel G. Colman M.S. Van Beveren C. Stacey K.J. Hume D.A. Maki R.A. Ostrowski M.C. Mol. Cell. Biol. 1996; 16: 538-547Crossref PubMed Scopus (318) Google Scholar), C. elegans LIN-1 (41Tan P.B. Lackner M.R. Kim S.K. Cell. 1998; 93: 569-580Abstract Full Text Full Text PDF PubMed Scopus (165) Google Scholar) andDrosophila Yan and Pointed P2 (42O'Neill E.M. Rebay I. Tjian R. Rubin G.M. Cell. 1994; 78: 137-147Abstract Full Text PDF PubMed Scopus (591) Google Scholar) as well as the C. elegans winged-helix factor LIN-31 (41Tan P.B. Lackner M.R. Kim S.K. Cell. 1998; 93: 569-580Abstract Full Text Full Text PDF PubMed Scopus (165) Google Scholar) are phosphorylated by ERKs. c-Jun (43Derijard B. Hibi M. Wu I.H. Barrett T. Su B. Deng T. Karin M. Davis R.J. Cell. 1994; 76: 1025-1037Abstract Full Text PDF PubMed Scopus (2957) Google Scholar, 44Kyriakis J.M. Banerjee P. Nikolakaki E. Dai T. Rubie E.A. Ahmad M.F. Avruch J. Woodgett J.R. Nature. 1994; 369: 156-160Crossref PubMed Scopus (2415) Google Scholar) and NFAT4 (45Chow C.W. Rincon M. Cavanagh J. Dickens M. Davis R.J. Science. 1997; 278: 1638-1641Crossref PubMed Scopus (300) Google Scholar) are targets of JNK, while CHOP (46Wang X.Z. Ron D. Science. 1996; 272: 1347-1349Crossref PubMed Scopus (743) Google Scholar) is a nuclear substrate for p38 kinase. This picture is further complicated by the fact that several transcription factors have been shown to be the targets of more than one MAPK pathway. Elk-1, a member of the ternary complex subfamily of ETS proteins, is targeted by all three pathways, while SAP-1 is activated upon phosphorylation by ERK or p38 kinase (Ref. 47Yang S.H. Whitmarsh A.J. Davis R.J. Sharrocks A.D. EMBO J. 1998; 17: 1740-1749Crossref PubMed Scopus (268) Google Scholar and references therein). Furthermore, MEF2C is phosphorylated by both p38 kinase and ERK5/BMK1 (48Kato Y. Kravchenko V.V. Tapping R.I. Han J. Ulevitch R.J. Lee J.D. EMBO J. 1997; 16: 7054-7066Crossref PubMed Scopus (498) Google Scholar) and ATF-2 and ATFa are targets of both the JNK and p38 kinase pathways (49Gupta S. Campbell D. Derijard B. Davis R.J. Science. 1995; 267: 389-393Crossref PubMed Scopus (1339) Google Scholar). Here we report for the first time that a Pax family transcription factor is phosphorylated in vitro and in vivo by MAP kinases. We found that three of the four putative MAPK phosphorylation sites in the Pax6 TAD is phosphorylated by ERK and p38 kinase, but not JNK, in vitro. One of these sites, Ser413, is conserved in Pax6 proteins from sea urchin to man and is also phosphorylated in vivo following activation of ERK or p38 kinase. Transient transfection studies with the Pax6 TAD fused to the DNA-binding domain of GAL4 and in the context of the full-length Pax6 protein revealed that mutation of this site to alanine strongly decreased the transactivating potential. Co-transfection of Pax6 with constitutively active MEK1 (which activates ERK1 and -2) or p38 kinase together with constitutively active MKK6b enhanced transcriptional activation by Pax6. However, while the potent p38 kinase-mediated increase in transactivation (16-fold) was largely dependent on the integrity of the Ser413 phosphorylation site, ERK activation gave a more modest enhancement of transactivation (3-fold) which was only reduced by 30% when this site was mutated to alanine. This suggests that activation of p38 kinase has a more direct positive effect on transactivation due to phosphorylation of the Pax6 TAD at Ser413 while ERK activation is less efficient and acting more indirectly. HeLa cells (ATCC CCL 2) were grown in Eagle's minimum essential medium supplemented with 10% fetal calf serum (HyClone), nonessential amino acids (Life Technologies, Inc.), 2 mml-glutamine, penicillin (100 units/ml), and streptomycin (100 μg/ml). NIH 3T3 fibroblasts (passage 123) were purchased from the American Type Culture Collection (ATCC CRL 1658) and cultured in Dulbecco′s modified Eagle′s medium supplemented with 10% calf serum (HyClone, Logan, Utah), penicillin (100 units/ml), and 100 μg/ml streptomycin (Life Technologies, Inc.) GAL4-Pax6 fusions were made by cloning parts of the zebrafish Pax6 coding region in-frame with the DNA-binding domain of yeast GAL4(1–147) in pSG424 (50Sadowski I. Ptashne M. Nucleic Acids Res. 1989; 17: 7539Crossref PubMed Scopus (472) Google Scholar). All GAL4-Pax6 fusion constructs are named according to the included parts of the Pax6 protein with the amino acid positions shown in parentheses. GAL4-Pax6(174–437) was made by cloning the 1239-base pairPmlI-XbaI fragment of Pax6 into theSmaI-XbaI sites of pSG424. The 640-base pairMboII fragment containing the C-terminal TAD of Pax6 was inserted into the SmaI site of pSG424 to give GAL4-Pax6(299–437). GAL4-Pax6(299–395) was made from the 299–437 construct by deleting an internal NdeI-SacI fragment followed by religation. Similarly, GAL4-Pax6(299–374) was constructed by deleting the SpeI-SacI fragment from GAL4-Pax6(299–437). To construct GAL4-Pax6(299–352) aHindIII-SacI fragment was deleted from GAL4-Pax6(299–437). GAL4-Pax6(353–437) was made by ligation of aHindIII (made blunt)-XbaI fragment into theBamHI (made blunt)-XbaI sites of pSG424. GAL4-Pax6(374–437) was constructed from GAL4-Pax6(299–437) by deletion of the SpeI (made blunt)-HindIII fragment and ligation of the rest of the vector to aHindIII-SacI (made blunt) fragment from pSG424. GAL4-Pax6(396–437) was also derived from GAL4-Pax6(299–437) by deleting the NdeI (made blunt)-HindIII fragment followed by ligation of the rest of the vector to aHindIII-SmaI fragment from pSG424. GAL4-Pax6(374–395) was made from GAL4-Pax6(374–437) by cutting it with NdeI and SacI, making the ends blunt and religating them. GAL4-Pax6(353–374) was derived from GAL4-Pax6(353–437) by digestion with SpeI andXbaI, making the ends blunt, and religating them. The GAL4-Pax6(353–395) construct was made from GAL4-Pax6(353–437) by deletion of the NdeI-XbaI fragment followed by religation of the rest of the plasmid. GAL4-Pax6(Δ375–395) was derived from GAL4-Pax6(299–437) by an internal deletion of theNdeI-SpeI fragment. GAL4-Pax6(Δ353–375) was also made by an internal deletion of GAL4-Pax6(299–437) employing theHindIII and SpeI sites. Specific PCR primers (G4-P6(299) and pSG424.3′; see TableI) were used to transfer selected Pax6 constructs from pSG424 to pFA-CMV (Stratagene), where the expression of the GAL4-Pax6 fusions is driven by a CMV promoter. All constructs were verified by sequencing and the expression and correct sizes of fusion proteins following transfection of HeLa cells were verified by Western blotting.Table ISequences of oligonucleotides used as polymerase chain reaction primers for plasmid constructions and site-directed mutagenesis and as double-stranded binding site probes in gel mobility shift assaysNameSequenceG4-P6(299)5′-GCCGGGATCCCCTAATTCCTCAAGT-3′pSG424.3′5′-TGATCATTACTTATCTAGAGCTCGAATTC-3′5eukGST5′-ATAGGCTAGCCATGGCCCCTATACTAGGTTATTGG-3′3eukGST5′-ATTCACGCGTCCGCTATCGCTACGTGAC-3′S413E5′-CGG-GTT-TAA-TCG-AAC-CTG-GAG-TGT-CTG-3′T388E5′-CTA-TGA-CAC-ATA-CGA-ACC-CCC-GCA-C-3′S413A5′-CGG-GTT-TAA-TCG-CAC-CTG-GAG-TGT-C-3′S376E5′-GTT-GCC-CAC-TGA-ACC-TTC-AGT-AAA-CG-3′T388A5′-CTA-TGA-CAC-ATA-CGC-ACC-CCC-GCA-C-3′S376A5′-GTT-GCC-CAC-TGC-TCC-TTC-AGT-AAA-CG-3′T375A/S376A5′-CAT-GTT-GCC-CGC-TGC-TCC-TTC-AGT-AAA-C-3′T322A/T323A5′-CCC-TCA-GCC-CGC-AGC-GCC-AGT-ATC-C-3′P6CONbs5′-TGGAATTCAGGAAAAATTTTCACGCTTGAGTTCACAGCTCGAGTA-3′ Open table in a new tab The GST-Pax6(353–437) construct was made by ligating theHindIII (made blunt)-EcoRI Pax6 fragment into theSmaI-EcoRI site of pGEX-3X (Pharmacia). GST-Pax6(299–437) was constructed by inserting a 640-base pairEcoRI fragment from GAL4-Pax6(299–437) into theEcoRI site of pGEX-1 (Pharmacia). The Pax6 expression vector pCI-Pax6 and the reporter vectors pG5E1bTATA-CAT, pTKG5CAT, and pG5E1bTATA-LUC have been described previously (18Nornes S. Clarkson M. Mikkola I. Pedersen M. Bardsley A. Martinez J.P. Krauss S. Johansen T. Mech. Dev. 1998; 77: 185-196Crossref PubMed Scopus (126) Google Scholar, 51Nornes S. Mikkola I. Krauss S. Delghandi M. Perander M. Johansen T. J. Biol. Chem. 1996; 271: 26914-26923Abstract Full Text Full Text PDF PubMed Scopus (66) Google Scholar). In vitro mutagenesis was performed according to the instruction manual for the "Quick-Change Site-Directed Mutagenesis Kit" (Stratagene). All mutagenized constructs were checked by sequencing. The specific mutagenesis primers used are shown in Table I. GST-Pax6 fusion proteins were purified from Escherichia coli LE392 extracts using glutathione-agarose beads (Pharmacia). The proteins were not eluted, but left on the beads and stored at 4 °C in phosphate-buffered saline containing 1% Triton X-100. To equalize the amounts of proteins used in the kinase assays the concentrations of GST fusion proteins were estimated by Coomassie Blue staining after sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The beads were washed twice with the respective kinase buffers before usein vitro kinase assays. GST-Pax6-containing agarose beads (5–20 μl) were mixed with either: 1) 2 μl of 10 × MAPK buffer (500 mm Tris-Cl, pH 7.5, 100 mmMgCl2, 10 mm dithiothreitol, 10 mmEGTA), 2 μl of 1 mm ATP, 0.5 μl of [γ-32P]ATP (100 μCi/μmol), and 1 unit of recombinant active ERK2 kinase (New England Biolabs) in a total volume of 20 μl, or with 2) 4 μl of 10 × p38 kinase reaction buffer (250 mm Hepes, pH 7.5, 100 mm magnesium acetate), 500 μm ATP, 0.5 μl of [γ-32P]ATP (100 μCi/μmol), and 1 μl (1 μg) of recombinant active p38 kinase (Stratagene) in a total volume of 40 μl. The reactions were left at 30 °C for 30 min, flicking the tubes every fifth min. The agarose beads were subsequently washed with 500 μl of phosphate-buffered saline (PBS) before boiling in 25 μl of 2 × SDS-PAGE gel loading buffer. The proteins were loaded on a 10% SDS-polyacrylamide gel, and run at 20 mA for 1.5–2 h in a Tris glycine buffer. The gel was dried, and exposed for autoradiography. Assays with c-Jun N-terminal kinase (JNK) was performed as described previously (52Westwick J.K. Brenner D.A. Methods Enzymol. 1995; 255: 342-359Crossref PubMed Scopus (46) Google Scholar). Subconfluent NIH3T3 cells were transfected with 10 μg of pCI-GST-Pax6(353–437) or phosphorylation site mutants in 10-cm diameter cell culture dishes using LipofectAMINE (Life Technologies, Inc.) according to the instructions of the manufacturer. Following 4 h of incubation with DNA, the cells were washed 3 times in PBS and left for 8 h in Dulbecco's modified Eagle's medium supplied with 0.1% serum. After 3 washes in Tris-buffered saline, pH 7.5, the cells were left for 30 min in phosphate-free Dulbecco's modified Eagle's medium (ICN) containing 0.1% dialyzed newborn calf serum, 25 mm Hepes, pH 7.5, and 2 mml-gluthamine and labeled for 8 h by adding 1 mCi/ml [32P]orthophosphate (Amersham). Some of the dishes were stimulated by adding dialyzed serum to 10% for 15 min. The culture dishes were placed on ice, washed twice in ice-cold PBS, and the cells were harvested by scraping in 1 ml of RIPA buffer (PBS containing 1% Nonidet P-40, 0.5% deoxycholate, 0.1% SDS with added protease and phosphatase inhibitors as described previously (53Bjørkøy G. Perander M. Øvervatn A. Johansen T. J. Biol. Chem. 1997; 272: 11557-11565Abstract Full Text Full Text PDF PubMed Scopus (68) Google Scholar)). Cleared lysates were mixed with 100 μl of 50% slurry of gluthatione-agarose beads (Pharmacia) and incubated at 4 °C for 1 h on a rotating wheel. The beads were then washed 8 times in phosphate-buffered saline containing 1% Triton X-100 and the final pellet was resuspended in 40 μl of 2 × SDS-PAGE gel loading buffer and boiled for 5 min. The labeled phosphoproteins were separated on a 10% polyacrylamide gel, electrotransferred onto a polyvinylidene difluoride (PVDF) membrane (Millipore), and visualized directly by autoradiography. Quantitation of the signals was performed using a PhosphorImager (Molecular Dynamics). Indirect detection of phosphorylation at serine 413 by monitoring a mobility shift was done by Western blotting using polyclonal Pax6 (P6C) or GST antibodies as described below. For [35S]methionine/cysteine labeling of proteins the cells were left for 30 min in methionine/cysteine-free Dulbecco's modified Eagle's medium (Sigma) containing 25 mm Hepes, pH 7.5, 2 mml-glutamine, and 10% dialyzed newborn calf serum before adding 35S-labeled amino acids (0.1 mCi/ml; Amersham) for 4 h. GST fusion proteins were purified as described above. Following purification the samples were split in two, half of the sample were resuspended in 2 × SDS-PAGE gel loading buffer and the other half was washed twice in λ-phosphatase assay buffer (New England Biolabs) before addition of 1000 units of λ-phosphatase (New England Biolabs) in a total volume of 25 μl. The dephosphorylation was stopped after a 30-min incubation at 30 °C by adding 10 μl of 5 × SDS-PAGE gel loading buffer. The samples were boiled and proteins were separated on a 10% SDS-polyacrylamide gel, electrotransferred onto a PVDF membrane, and visualized by autoradiography using Kodak BioMax MR film. For phosphorylation shift analyses using Western blot detection subconfluent cell cultures of NIH3T3 or HeLa cells were transfected with 10 μg of the different expression vectors using LipofectAMINE as described above for NIH3T3 cells or calcium-phosphate coprecipitation for HeLa cells. After 16 h of serum deprivation (0.1% serum) the cells were stimulated with 10% serum or 100 ng/ml phorbol ester (TPA, Sigma) for the indicated times. GST fusion protein purification and SDS-PAGE were performed as described above. Following electrotransfer onto PVDF membranes the proteins were detected using polyclonal anti-GST or anti-Pax6 antibodies (P6C) as described below. For p38 kinase-mediated in vivo phosphorylation, 10 μg of GAL4-Pax6(299–437) TAD fusion constructs (wild-type and mutants) in the pFA-CMV expression vector (Stratagene) were co-transfected with 5 μg of p38 kinase (54Zhang S. Han J. Sells M.A. Chernoff J. Knaus U.G. Ulevitch R.J. Bokoch G.M. J. Biol. Chem. 1995; 270: 23934-23936Abstract Full Text Full Text PDF PubMed Scopus (653) Google Scholar) and 5 μg of MKK6b(EE) (55Han J. Lee J.-D. Jiang Y. Li Z. Feng L. Ulevitch R.J. J. Biol. Chem. 1996; 271: 2886-2891Abstract Full Text Full Text PDF PubMed Scopus (482) Google Scholar) expression vectors or pcDNA3-HA (vector control) into NIH-3T3 cells using either Fugene 6 (Roche Molecular Biochemicals) or LipofectAMINE Plus (Life Technologies, Inc.). For ERK-mediated in vivophosphorylation, 10 μg of GAL4-Pax6 TAD fusion constructs and 5 μg of expression vector for an activated mutant of MEK1, MEK1(EE) (56Cowley S. Paterson H. Kemp P. Marshall C.J. Cell. 1994; 77: 841-852Abstract Full Text PDF PubMed Scopus (1854) Google Scholar), or the respective vector control was used in co-transfections. In vivo labeling with [32P]orthophosphate was done essentially as described above with the exception that the cells were harvested in HA lysis buffer (50 mm Tris-HCl, pH 7.5, 150 mm NaCl, 2 mm EDTA, 1 mm EGTA, 1% Triton X-100) for experiments with p38 kinase and JNK lysis buffer (25 mm Hepes, pH 7.7, 300 mm NaCl, 1.5 mm MgCl2, 0.2 mm EDTA, 0.15 Triton X-100) for experiments with activated MEK1. Both lysis buffers contained the following inhibitors: 20 mm p-nitrophenyl phosphate, 50 mm sodium fluoride, 50 μm sodium vanadate, 5 mm benzamidine, 0.5 μg/ml leupeptin, 2 μg/ml aprotinin, 20 mmβ-glycerophosphate, 0.5 mm phenylmethyl sulfonate, 0.7 μg/ml pepstatin A. Polyclonal anti-GAL4 DBD antibodies and protein A/G-Sepharose beads (both from Santa Cruz Biotechnology) were used for immunoprecipitation of the GAL4-Pax6 fusion proteins. The beads were washed 3 times with the lysis buffer before boiling in 30 μl of gel-loading buffer and electrophoresis on a 10% SDS-polyacrylamide gel. The proteins were blotted onto a PVDF membrane and32P-labeled proteins were detected by aut